CD-Tagging: A New Approach to Gene and Protein Discovery and Analysis - J.W. Jarvik; S.A. Adler; C.A. Telmer; V. Subramaniam; A.J. Lopez (BioTechniques)
We describe a new method for gene discovery and analysis, CD-tagging, that puts specific molecular tags on a gene, its transcript and its protein product. The method has been successfully tested in two organisms, the haploid unicellular alga Chlamydomonas reinhardtiiand the metazoan Drosophila melanogaster. The method utilizes a specially designed DNA molecule, the CDcassette, that contains splice acceptor and donor sites surrounding a short open reading frame. Insertion of the CD-cassette into an intron in a target gene introduces a new exon, represented by the open reading frame of the CD-cassette, surrounded by two functional hybrid introns. As a result (i) the gene is tagged by a specific nucleotide sequence, (ii) the mRNA is tagged by a specific nucleotide sequence and (iii) the protein is tagged by a specific peptide sequence. Because these tags are unique, specific nucleotide or antibody probes can be used to obtain and/or analyze the gene, transcript or protein. As a gene discovery technology, CD-tagging has two unique advantages: 1) Genes can be identified through a primary screen at the protein level, and so the very process by which a gene is identified provides specific empirical information about its biological function. 2) The cassette arms, which are spliced out of the transcript of the target gene, are available to carry a wide variety of DNA sequences, such as genes encoding drug resistance that can be used to select for the presence of the CD-cassette in the genome.